A parametric study of a concentrating integral storage solar water heater for domestic uses. (25th January 2017) - Varghese, Jaji; Samsher,; Manjunath, K.
Highlights: BSWH with a CPC reflector having a wider acceptance angle proposed. Additional thermal resistance added by introducing an air gap at the arms of CPC. Percentage reduction of heat loss from 13.4% to 52.5% with provision of air gap. Mass flow rate effect less dominant, system delivers water between 45 °C and 55 °C. Best suited for domestic applications, an alternative to FPC/ETC SWH's. Abstract: A parametric study of a concentrating integrated collector storage solar water heater was undertaken. The concentrator used was the Compound Parabolic Concentrator (CPC), an optical non-imaging device, a wider acceptance angle was used (64°) so that only occasional tracking is needed making this suitable for household purposes. The reflective concentrator was supported on a wooden cradle which comprised the two parabolas of the compound parabolic concentrator. Unlike conventional CPC systems with a large number of smaller diameter tubes, here is a single larger diameter drum was positioned at the focus of the CPC. Experimental studies were carried out and the mean collector efficiency computed on the model with an air gap introduced in the side walls (arms of the CPC). The parametric study of the design by EES at solar noon was in good agreement with the collected experimental results. The maximum thermal efficiency of the collector was 38% and the maximum water temperature attained was 53 °C.